Information technology : - Senn, James A. (Pearson Prentice Hall, 2004)
The emphasis is on the way information technology is used and applied for problem solving; the new and emerging technologies as they are being implemented in real organizations; applications to personal and professional practice; and the challenges and opportunities of IT in international business situations. Beginning with an introduction to Information Technology, this book covers hardware, database, and network technologies; IT applications development; and current Information Technology issues. Those interested in keeping current with the development and applications of Information Technology